A five-year observational prospective mono-center study of the efficacy of alemtuzumab in a real-world cohort of patients with multiple sclerosis - Sandgren, Sofia; Novakova, Lenka; Nordin, Anna; Axelsson, Markus; Malmeström, Clas; Zetterberg, Henrik; Lycke, Jan (Frontiers in Neurology, 2023)
Background: Alemtuzumab (ALZ) is a immune reconstitution therapy for multiple sclerosis (MS). Objective: To assess the long-term efficacy of ALZ in a real-world cohort of relapsing-remitting MS (RRMS) patients selected for ALZ. Methods: 51 RRMS patients [female = 31; mean age 36 (SD 7.1) years; median expanded disability status scale (EDSS) 2 IQR 1.5)] initiating ALZ, were consecutively included. Patients were assessed at baseline and thereafter annually for five years with clinical measures, Single Digit Modality Test (SDMT), and MRI. Glial fibrillary acidic protein (GFAP), reflecting astrogliosis, and neurofilament light (NfL), reflecting axonal damage, were measured in cerebrospinal fluid (CSF) and serum at baseline and after two years in CSF, and annually in serum. Control subjects were symptomatic controls (SCs, n = 27), who were examined at baseline and after five years without evidence of neurological disease. Results: While the mean annual relapse rate was significantly reduced from baseline at each year of follow-up, disability was essentially maintained at a median EDSS of 1.5 and IQR between 1.13-2.25. New MRI activity was recorded in 26 patients (53%) over five years. The proportion of patients who achieved no evidence of disease activity (NEDA-3), 6-months confirmed disability worsening (CDW), and 6-months confirmed disability improvement (CDI) at five years were 33%, 31%, and 31%, respectively. The SDMT score was reduced for patients (p < 0.001), but unchanged for SCs. ALZ treatment did not change GFAP levels, whereas there was a significant decrease for RRMS patients in median CSF and serum NfL levels at follow-up [CSF month 24: 456 pg/mL (IQR 285.4) (p = 0.05); serum month 24: 6.7 pg/mL (IQR 4.7) (p < 0.01); serum month 60: 7.2 pg/mL (IQR 4.7) (p < 0.01)], compared to baseline [CSF: 1014 pg/mL (IQR 2832.5); serum 8.6 pg/mL (IQR 17.4)].Conclusion: In this real-world mono-center population, we observed a progression-free survival of 69%, cumulative NEDA-3 of 33%, and reduced NfL levels, over a five-year follow-up. This confirms ALZ as an effective immune reconstitution therapy that significantly reduces neuro axonal loss, and therefore has the potential to reduce long-term neurological disability. ALZ did not appear to affect astrogliosis.